Pengaruh Kesadaran Wajib Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Samsat Ciledug : Studi Empiris Perpajakan Kendaraan Bermotor di Samsat Ciledug - Kusmaydi, Aurel Disa; Asmonah, Siti (Prisani Cendekia, 2025)
This study aims to analyze the effect of taxpayer awareness and tax sanctions on the compliance of motor vehicle taxpayers at Samsat Ciledug. The issue of non-compliance among taxpayers and complaints related to service quality at Samsat Ciledug serve as the main background of this research. A quantitative approach was employed, with data collected from motor vehicle taxpayers at Samsat Ciledug. The analytical method used was multiple regression analysis. The findings reveal that, simultaneously, taxpayer awareness and tax sanctions have a significant effect on taxpayer compliance, contributing 72.2% to the variation in compliance. Partially, taxpayer awareness is proven to have a positive and significant effect on motor vehicle taxpayer compliance. However, tax sanctions were found to have no significant effect on taxpayer compliance when tested individually. These results indicate that internal factors such as understanding and awareness of taxpayers play a more dominant role in encouraging compliance compared to external factors such as tax sanctions in the research context.